Analysis of pH, Temperature and DO of Vannamei Shrimp (Litopenaeus vannamei) Rearing Pond at PT. Biru Laut Nusantara, Pangandaran, West Java - Adam Setiawan (PT. Gyandharma Global Media, 2025)
Vannamei shrimp have advantages that make them ideal for cultivation. These advantages include high responsiveness to feed or large appetite, resistance to disease. One important aspect in intensive cultivation production is monitoring water quality parameters in shrimp ponds. Some of the main parameters that need to be considered for successful vannamei shrimp farming include pH, temperature, and dissolved oxygen (DO) levels. This study aims to analyze the effect of water quality, especially pH, temperature, and DO, on the growth of vannamei shrimp at PT. Biru Laut Nusantara, Pangandaran Regency, West Java. This study uses descriptive methods, observation, active participation, and surveys to describe a particular event or condition based on the symptoms and facts found. The data collection methods used are primary data and secondary data. There are two types of data collection based on their sources. The results of the study showed that water quality, especially temperature and DO in vannamei shrimp farming ponds, were at their optimum values. With a temperature value between 25-32oC and DO between 4.6 - 8.2. Meanwhile, the pH is between 7.5 – 9.0, this value is slightly higher than the pH standard but is still considered safe.